Pre-voters' Political Education Activities at the Election Smart House amidst the Covid-19 Pandemic - Hariyanti Hariyanti; Hambali Hambali; Ahmad Eddison; Jumili Ariyanto (Universitas of Muhammadiyah Makassar, 2022)
Pre-voters are a group that will prepare to become novice voters in the next few years; it is important to prepare them to become intelligent and rational voters, one of which is through the existence of the Election Smart House. The research design employed a qualitative descriptive method. The researcher describes in-depth and comprehensively the activities of pre-voter political education at the Election Smart House of the Pekanbaru City of General Elections Commission during the Covid-19 pandemic. Data collection was carried out through observation, interviews, and documentation. Research informants include the commissioner of the General Election Commission of Pekanbaru City, the Elecivicction Smart House of Pekanbaru City manager, and Pancasila and Civic Education teachers teaching at Senior High Schools in Pekanbaru City. The results showed that during the Covid-19 pandemic, from 2020 until now, the activities in the Election Smart House were not very active. It was noted that during the pandemic in the last two years, there were no visits from students to the Election Smart House of the Pekanbaru City owned by the General Elections Commission or visits from the City’s Election Smart House to high schools in Pekanbaru. Therefore, to overcome this situation, the Election Smart House manager initiated a creative idea by procuring Voter Education Podcasts in the Election Smart House by inviting resource persons and broadcasting them through the Pekanbaru City KPU (General Election Commission) YouTube channel. This activity is one way to educate the public without violating the health protocol and an effort to keep the Election Smart House as the center of community political education, especially students as pre-voters.